Etika Penggunaan Artificial Intelligence (AI) dalam Keputusan Bisnis - Puspa Devina; Haryati Isnaini; Rahma Aulia; Winda Eryani; Razkia Asmarani; Dwi Riama; Annisa Aulia Yasmin (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Advances in Artificial Intelligence (AI) have driven a transformation in business decision-making processes through its ability to perform fast, accurate, and predictive data analysis. While AI can improve operational efficiency, productivity, and the quality of decisions, its use also raises various ethical challenges that must be addressed. This study aims to analyze the benefits, challenges, and ethical implications of using AI in business decision-making. The method used is a literature review, examining eight relevant national scientific articles published between 2024 and 2026. The data were analyzed descriptively through a process of identifying, selecting, and synthesizing research findings. The results indicate that AI plays a crucial role in enhancing decision-making effectiveness through business process automation, data analysis, and predictive capabilities. However, the implementation of AI also faces various ethical challenges, such as algorithmic bias, a lack of transparency and accountability, and risks to privacy and data security. Furthermore, the implementation of AI governance, algorithmic audits, and human oversight are critical factors in supporting the responsible use of AI. This study concludes that organizations need to balance the use of AI technology with the application of ethical principles to create transparent, fair, and sustainable decision-making systems.